46 The role of coronary computed tomography angiography identifying coronary artery disease in patients with chest pain in a peripheral hospital in ireland. (October 2018) - Buckley, J; Hafiz, H; Hayes, J
Abstract : Introduction: The aim of this study was to assess the clinical role of CCTA in assessing CAD in patients with chest pain in Cavan General Hospital, RCSI Hospital Group. Background: Chest pain is a frequent clinical presentation to an emergency department. CCTA correctly identify those with CAD has become ever more relevant. NICE guidelines recommend CCTA as the first line diagnostic test in the assessment of CAD 1. Methods: A single centre retrospective review of the results of CCTA in those presenting with chest pain from March 2015 to December 2017. All patients underwent a non-enhanced calcium scan and a CCTA. The degree of stenosis on CCTA was compared to results of those who were identified as requiring invasive coronary angiography (ICA). All patients who presented with typical chest pain reported within a calendar year. Data was extracted from patient records, hospital in patient enquiry (HIPE) and from order procurement data. Information was recorded on age, date of imaging, risk factors for CAD, degree of stenosis, calcium scoring and recommended follow up. Results: A total of 29 patients underwent CCTA. The age of patients ranged from 34–83 years and the majority had more than one risk factor 16 (55%). The majority received their imaging within three weeks of referral. 22 patients (76%) with reassuring results showing no obstructive plaques and did not require further intervention. 3 patients (10%) images revealed pulmonary nodules and were recommended for follow up. One patient showed bihilar adenopathy, mediastinal adenopathy and fibrotic changes in the right lower lung with subsequent respiratory follow up. 7 patients (24%) were referred for ICA. Two patients (7%) were referred for ICA on the basis of a high Agaston score, with moderate stenosis on CCTA. Subsequent ICA, showed approximately 40% stenosis and for medical management. One patient (3%) with extensive calcified and non-calcified stenosis on CCTA had percutaneous coronary intervention to the lesions. CCTA identified one patient (3%) with three-vessel coronary artery disease and a large ascending aortic aneurysm. This patient had coronary artery bypass grafting and a metallic aortic root with valve replacement. Of the 7 patients referred for angiography, three are still awaiting their procedure with an average waiting time of six months. CCTA was carried out in two private institutions. The average cost was €565, range €325–650. 1121 patients presented to Cavan General Hospital with cardiac type chest pain in 2017. Their average length of stay was 2.72 days. This compares with diagnostic ICA with an average cost of €1500. Baseline Demographics table 1 N(%) Male sex 20(69) Median age 54 Hypertension 9(31) Diabetes 2(7) Smoker 8(28) Hyperlipidaemia 7(24) Family history of IHD 11(38) BMI>30 3(10) Discussion Exercise ECG has a low sensitivity in diagnosing CAD, ranging between 45%–50% 2, 3. This leads to a significant proportion of at risk patients being missed while others with normal coronary vessels undergoing unnecessary ICA. Recent ESC guidelines recommend those with an intermediate pre test probability (PTP) of 15%–85% should undergo non-invasive testing 4. The high sensitivity (95%–99%) and high negative predictive value (97%–99%) of CCTA may reassure patients and physicians 5, 6. Our study highlighted this finding with the majority, 22 (76%)receiving reassurances with no further intervention required. Therefore CCTA is recommended for patients with low intermediate PTPs. The ESC guidelines highlight there may be over diagnosis in patients with Agaston scores of >400 3. This is reflected in our findings whereby two patients with high Agaston scores who were referred for ICA did not show significant obstructing lesions. Our analysis indicates CCTA is a robust method for diagnosing CAD in an intermediate PTP group and is a useful tool for screening of coronary stenosis. CCTA in a peripheral hospital setting allows for rapid assessment with an average waiting time of three weeks. Correct identification of patients for CCTA with subsequent reassuring results will inevitably reduce the necessity of referral for invasive angiography. CCTA reduces the expenditure of hospital stays and additional costs from ICA. CCTA should be considered in hospitals where direct access to ICA is not available. It reduces patient bed days, allows efficient patient assessment and has proven cost effectiveness.